Reúso de frameworks transversais com apoio de modelos - Gottardi, Thiago (2012)
Aspect-Oriented programming was created to modularize the so-called crosscutting concerns . Crosscutting concerns have some properties that cannot be fully modularized with the object-oriented paradigm. After that, aspect-oriented frameworks were created in order to make reuse of different concern codes easier. Among these frameworks, Crosscutting Frameworks are aspect-oriented frameworks specifically created for crosscutting concern code modularization, for instance, persistence, distribution, concurrency and business rules. Currently, these frameworks are usually distributed as source code and must be reused by extending classes, aspects and methods. Reusing these frameworks in code-level require application developers to worry about implementation issues, that affects understandability, productivity and quality of final software. In this thesis, the objective is to raise abstraction level by applying a new model-driven approach for crosscutting framework reuse, which also allows reusability during earlier development phases. Experiments were conducted in order to compare the productivity of the proposed process with the conventional reuse technique, which is based on source-code edition. It was identified that the proposed process has advantages during the reuse activity, however, no advantages were detected while maintaining an application coupled to a crosscutting framework.